Immune cell infiltrates as prognostic biomarkers in pancreatic ductal adenocarcinoma: a systematic review and meta‐analysis - Andrew J McGuigan; Helen G Coleman; R Stephen McCain; Paul J Kelly; David I Johnston; Mark A Taylor; Richard C Turkington (Wiley, 2021)
Abstract Immune cell infiltration has been identified as a prognostic biomarker in several cancers. However, no immune based biomarker has yet been validated for use in pancreatic ductal adenocarcinoma (PDAC). We undertook a systematic review and meta‐analysis of immune cell infiltration, measured by immunohistochemistry (IHC), as a prognostic biomarker in PDAC. All other IHC prognostic biomarkers in PDAC were also summarised. MEDLINE, EMBASE and Web of Science were searched between 1998 and 2018. Studies investigating IHC biomarkers and prognosis in PDAC were included. REMARK score and Newcastle-Ottawa scale were used for qualitative analysis. Random‐effects meta‐analyses were used to pool results, where possible. Twenty‐six articles studied immune cell infiltration IHC biomarkers and PDAC prognosis. Meta‐analysis found high infiltration with CD4 (hazard ratio [HR] = 0.65, 95% confidence interval [CI] = 0.51-0.83.) and CD8 (HR = 0.68, 95% CI = 0.55-0.84.) T‐lymphocytes associated with better disease‐free survival. Reduced overall survival was associated with high CD163 (HR = 1.62, 95% CI = 1.03-2.56). Infiltration of CD3, CD20, FoxP3 and CD68 cells, and PD‐L1 expression was not prognostic. In total, 708 prognostic biomarkers were identified in 1101 studies. In summary, high CD4 and CD8 infiltration are associated with better disease‐free survival in PDAC. Increased CD163 is adversely prognostic. Despite the publication of 708 IHC prognostic biomarkers in PDAC, none has been validated for clinical use. Further research should focus on reproducibility of prognostic biomarkers in PDAC in order to achieve this.